Change in the fatty acids spectrum of erythrocyte in patients with chronic form of coronary heart disease in treatment by Simvastatin - V. V. Novitsky; M. Yu. Kotlovsky; D. A. Kirichenko; R. S. Karpov; Yu. V. Kotlovsky; I. Yu. Yakimovich (Бюллетень сибирской медицины)
The research of unsaturated and saturated of fatty acids (UFAand SFA) in the erythrocytes in men and women with chronic ischemic heart disease was done by the method of a gas-liquid chromatography-mass spectrometry before and after simvastatin intake. Increase in the ratio of ω3 / ω6 FA at the expence of reducing of the rate of ω6 UFAwas revealed  in men after treatment for 2 months which is the condition for the changing of type of synthesized eicosanoids. The decrease in the total content of ω6 and ω9 UFAled to the fall in the amount of the UFAin both sexes, despite of the heightened rate of amount of ω7 UFAin women. The treatment led to the increasing of saturated FA amount (SFA) and it led to the decrease of unsaturation index FA on the back of the reduction of nonsaturated fatty acids level (NFA). The results confirm the presence of lipid-lowering effect of Simvastatin, but there is a need for therapy, taking into account of the normalization of the exchange FA in patients with chronic coronary ischemic heart disease.